Lithofacies Features of the Botuobinsky Horizon of the Southeastern Part of the Srednebotuobinskoye Oil and Gas Condensate Field (Eastern Siberia) - D. O. Smirnova; A. V. Mordasova; N. I. Korobova; V. Yu. Bliznyukov; R. S. Sautkin; M. E. Voronin; N. V. Alekseev (Georesursy, 2025)
The article presents the results of the lithofacies study of the Late Vendian Botuobinsky horizon of the southeastern part of the Srednebotuobinskoye field. The main problem solved in the article is the search for intervals with the best reservoir properties within the Botuobinsky horizon and the forecast of their distribution over the area of the Srednebotuobinskoye field using complex lithofacies and cyclic analysis. Based on the description of the core, thin sections, X-ray phase analysis, X-ray fluorescence spectrometry, structural, texture, granulometric analyses and geophysical well logging, a lithofacies scheme was constructed for the time of formation of the Botuobinsky horizon and the horizon was divided into four cyclites. The best reservoir characteristics within the Botuobinsky horizon were established in its middle part (2–3 cyclites) in the deposits of the coastal slope facies, tidal channels and sandy littoral. However, the primary filtration-capacity properties of the Botuobinsky horizon were significantly influenced by secondary processes of salinization, quartz regeneration, anhydritization and dolomitization, which, however, are manifested differently in different facies.